2014
DOI: 10.1080/15524256.2014.938890
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Social Work Students Toward End-of-Life Care Planning

Abstract: This study examined the attitudes of social work students toward end-of-life care planning, as well as their degree of willingness to engage in this area of social work practice. Factors associated with their attitudes were measured through structured surveys completed by 102 social work students (N = 102) at a school of social work in the southeast. Results indicated that these social work students tended to have positive attitudes toward end-of-life care planning in general. Moreover, these attitudes were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Twenty studies used cross-sectional surveys, three used qualitative interviews [24–26], and the remaining eight were interventional studies [2734]. Sixteen descriptive studies included a sample of only social workers [11, 19, 20, 22, 24, 25, 3544]. Of them, four included social workers recruited from hospitals, additional four included social workers from nursing homes, two included social worker students, and the remaining six included a mixed sample of social workers (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty studies used cross-sectional surveys, three used qualitative interviews [24–26], and the remaining eight were interventional studies [2734]. Sixteen descriptive studies included a sample of only social workers [11, 19, 20, 22, 24, 25, 3544]. Of them, four included social workers recruited from hospitals, additional four included social workers from nursing homes, two included social worker students, and the remaining six included a mixed sample of social workers (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…68% of the respondents reported that social workers were responsible for documenting ACP.4. Compared with those at other care settings, oncology and inpatient palliative care social workers were less likely to be responsible for ensuring that patients/families are informed of ACP options and documenting ACP preferences.Kwon et al, 2014 [11] (USA)To examine the attitudes of social work students toward EoL care planning,A cross-sectional surveyA cluster sample of social work students at a school1021. 72% of the participants indicated that they felt comfortable discussing the topic of death.2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations